KAJIAN KONEKTIFITAS ANTAR PULAU DI WILAYAH KEPULAUAN RIAU - Ronaldy Lovina (Jurnal Potensi, 2022)
Human civilization is caused by a nomadic life from one place to another with the aim of finding a decent life. By moving a person or group of people will add to the association, so that will make the way of life more advanced. So that an area is formed and supporting facilities and infrastructure are built to meet the needs. Due to the density of an area due to human development and increasing needs, it is necessary to find new arable land, land needs such as agriculture, education, industry and others. The location sought is usually seen from a strategic location such as close to the river or the coast. In areas characterized by islands, life generally begins at the edge of the coast or waters because it can provide convenience in meeting food needs such as marine and fishery activities and the results are also easier to market. Regional development in the coastal area with the aim of gaining access to each area will have an impact on the trade system between regions, regions and countries. To accelerate the development and trade system in the archipelagic region in the current era of globalization, what is really needed is accessibility and an integrated transportation system, both land, sea and air transportation, so that it can improve connectivity or assemble islands to knit the country so that an archipelagic region is developed and capable of being developed. compete in the era of globalization. The availability of smooth, safe and comfortable transportation facilities and infrastructure to facilitate the movement of each person or group so that it has an impact on regional development and can reduce disparities between regions in the Negeri segantang lada.